Solid substrate fermentation (SSF) and submerged fermentation (SmF) of aspergillus versicolor A6 using pineapple waste as substrate for pectinase production - Siti Ratna, Binti Mustafa (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Pineapple waste was an agricultural waste that used as substrate for the production of pectinase via fermentation. This project was aimed to produce and determine the optimum condition for pectinase production by Aspergillus versicolor A6 under different types of fermentation system; solid substrate fermentation (SSF) and submerged fermentation (SmF). Four parameters were being studied; time of incubation, temperature, pH and size of inoculums. In this study, the optimum condition for pectinase production of solid substrate fermentation was recorded at day 4 (96 hours) of time of incubations, 30°C of temperature, pH 5.5, addition of CaCl2 in the medium and inoculated with 108 spore suspension/ml. The optimum condition for submerged fermentation was the same as the solid substrate fermentation but different on optimal time of incubations which was recorded the highest at day 2 (48 hours). The enzyme was extracted and assayed by using DNS method in order to determine the total amount of reducing sugar produced.